Design of Porous Metal Block Augmentation to Treat Tibial Bone Defects in Total Knee Arthroplasty Based on Topology Optimization - Liu, Yang; Chen, Bingpeng; Wang, Chenyu; Chen, Hao; Zhang, Aobo; Yin, Weihuang; Wu, Naichao; Han, Qing; Wang, Jincheng (Frontiers in Bioengineering and Biotechnology, 2021)
The metal block augmentation, which is used for the treatment of tibial bone defects in total knee arthroplasty, with high stiffness will cause significant alteration in stress distribution, and its solid structure is not suitable for osseointegration. This study aimed to design a porous block to reduce weight, promote bone ingrowth, and improve its biomechanical performance. The metal block augmentation technique was applied to finite element models of tibial bone defects. Minimum-compliance topology optimization subject to the volume fraction combined with the porous architecture was adopted to redesign the block. Biomechanical changes compared with the original block were analyzed by finite element analysis. The stress distribution of the block and proximal tibia were recorded. The strain energy density of the proximal tibia was obtained. The newly designed block realized 40% weight reduction. The maximum stress in the optimized block decreased by 11.6% when compared with the solid one. The maximum stress of the proximal tibia in the optimized group increased by 18.6%. The stress of the anterior, medial, and posterior parts of the proximal medial tibia in the optimized group was significantly greater than that in the original group (all p < 0.05). The optimized block could effectively improve the biomechanical performance between the block and bone. The presented method might provide a reference for the design of customized three-dimensional-printed prostheses.